A Steam Ejector Refrigeration System Powered by Engine Combustion Waste Heat: Part 1. Characterization of the Internal Flow Structure - Yu Han (Applied Sciences, 2019)
With the escalating production of automobiles, energy efficiency and environmental friendliness have always been a major concern in the automotive industry. In order to effectively lower the energy consumption of a vehicle, it is essential to develop air-conditioning systems that can make good use of combustion waste heat. Ejector refrigeration systems have become increasingly popular for this purpose due to their energy efficiency and ability to recycle waste heat. In this article, the elements affecting the performance of a typical ejector refrigeration system have been explored using both experimental and numerical approaches. For the first time, the internal flow structure was characterized by means of comprehensive numerical simulations. In essence, three major sections of the steam ejector were investigated. Two energy processes and the shock-mixing layer were defined and analyzed. The results indicated that the length of the choking zone directly affects the entertainment ratio under different primary fluid temperature. The optimum enterainment ratio was achieved with 138 °C primary fluid temperature. The shock-mixing layer was greatly affected by secondary fluid temperature. With increasing of back pressure, the normal shock gradually shifted from the diffuser towards the throat, while the shock train length remains lunchanged.